صيغ الأمر في" كتاب الأدب"من صحيح البخاري - Memoona Aman; Ammara Gulzar (Pakistan Journal of Islamic Research)
An Imperative verb is the most important verb in grammar. It is an action word which gives a command, and used to instruct someone as what to do. Semantics contain all the meanings of an Imperative verb which explains its different explanations as per reference to the text which contained it. It indicates a deep connection between grammar and semantics. In Arabic grammar an Imperative verb has four types and each type has its own individual semantically meanings. The ultimate reliable sources in Arabic language is Holy Qurʼān and the sayings of Holy Prophet Muhammad (Peace Be upon Him), because of its precise significance and consistency. The grammatical and semantically structures carry many meanings of sayings of the Holy Prophet Muhammad (Peace Be Upon Him). This study leads to understand the meaning of an Imperative verb grammatically and semantically in the light of sayings of Holy Prophet Muhammad (Peace Be Upon Him). Sayings of the Holy Prophet Muhammad (Peace Be Upon Him) contain imperative verbs in abundance, and every imperative verb has its own semantically meaning which effects on the text explanations.